Implementasi Media Video Sebagai Sarana Peningkatan Kesadaran K3 di SMK NU Muara Padang Kabupaten Banyuasin: Studi Quasi Eksperimen - Dina Waldani; Eva Elfrida Pardede; Iin Seprina; Putri Alya Fitriani; Salsabila Oktarina (Faculty of Social Science, Universitas Negeri Padang, 2026)
Occupational Safety and Health (OSH) is an important component that cannot be separated from human activities, both in industrial and educational environments. There are still students who do not pay attention to occupational safety aspects in workshops, such as not wearing complete personal protective equipment (PPE) and not understanding safe work procedures. This condition shows that the level of OSH awareness among students is still low. This study aims to determine the effectiveness of video media in increasing student awareness of OSH. This study used a quantitative quasi-experimental design, with the research sample consisting of students majoring in light vehicle engineering and motorcycle engineering at SMK NU Muara Padang. The instruments used included an OSH awareness questionnaire, observation sheets, and educational videos. Data analysis was performed using univariate and bivariate analysis with a paired t-test. The results showed that the average knowledge score before the OSH promotion using videos was 38.69, and after the promotion, it was 44.69 (delta mean knowledge score of 6). The average attitude score before the K3 promotion using videos was 63.52 and after was 75.29 (delta mean attitude score of 1.77). The average K3 awareness score before the K3 promotion using videos was 52.60 and after was 60.94 (delta mean awareness score of 8.34). The results of the paired t-test show that there is a significant difference between K3 promotion using video media and the increase in knowledge (p=0.000) and attitude (p=0.000). Video media has been proven to be effective in increasing students' knowledge and attitudes about OSH. There is a need to develop other similar educational video media in the form of demonstration videos, especially regarding ergonomic work positions and prevention efforts, as well as improving occupational health and safety.